Inspirative Geology - The Influence of Natural Geological Formations and Patterns on Contemporary Landscape Design - Al Basha, Nawarah; Eplényi, Anna; Sándor, Gábor (Landscape Architecture and Art, 2021)
Throughout the history of landscape design, we have witnessed many examples where natural features were used as symbolic elements of manmade landscapes and gardens. This influence of landscape geology had its impact on contemporary landscape architecture, resulting in diverse and innovative applications, which are the main topic of our discussion. The article is intended to demonstrate the trend of drawing inspiration from natural landscape features in contemporary landscape architecture in a new and complex way, focusing particularly on the influence of geology, geomorphology and tectonics. A study was conducted on twelve available, published contemporary landscape projects from the last two decades analysing the imitation of nature in the designs, with photo documentation and description. The aim is to identify how ‘native geology’ can influence today’s landscape architecture, which formations are inspirative, where and how they are integrated to the contemporary artistic design. Furthermore, in order to develop a complex understanding on how these references applied to the sites enhance the experience of the space. The selected projects are compared according to pairs of contrasting qualities that are related to measurable characteristics of a space. This will finally lead to identifying some common trends of today’s landscape architecture in applying this geology-inspired design approach.